Case Report: Refractory Hypotension of GABA B Receptor Autoimmune Encephalitis - Hanxin, Kong; Xiaomin, Wang; Hao, Ying; Shuihong, Zheng (Frontiers in Neurology, 2020)
Introduction: With the development of antibody detection technology, GABA B receptor encephalitis is an increasingly recognized autoimmune mediated disease.This paper describes a patient with refractory hypotension who suffered from GABA B receptor autoimmune encephalitis. Case Report: We describe a 63-year-old man with GABA B receptor autoimmune encephalitis who had hypotension on day 17 of onset. Despite two rounds of immunoglobulin administration, high-dose intravenous steroid injections, and immunosuppressive therapy, on day 35 of hospitalization, psychiatric symptoms and seizures were significantly improved, but blood pressure remained low. Conclusion:The purpose of this case and literature review is to investigate the impairment of autonomic nerve function and its subsequent management in patients with GABA B receptor autoimmune encephalitis.